Chromosome-length genome assembly and linkage map of a critically endangered Australian bird: the helmeted honeyeater. (29th March 2022) - Robledo-Ruiz, Diana A; Gan, Han Ming; Kaur, Parwinder; Dudchenko, Olga; Weisz, David; Khan, Ruqayya; Lieberman Aiden, Erez; Osipova, Ekaterina; Hiller, Michael; Morales, Hernán E; Magrath, Michael J L; Clarke, Rohan H; et al.
Abstract: Background: The helmeted honeyeater ( Lichenostomus melanops cassidix ) is a Critically Endangered bird endemic to Victoria, Australia. To aid its conservation, the population is the subject of genetic rescue. To understand, monitor, and modulate the effects of genetic rescue on the helmeted honeyeater genome, a chromosome-length genome and a high-density linkage map are required. Results: We used a combination of Illumina, Oxford Nanopore, and Hi-C sequencing technologies to assemble a chromosome-length genome of the helmeted honeyeater, comprising 906 scaffolds, with length of 1.1 Gb and scaffold N50 of 63.8 Mb. Annotation comprised 57, 181 gene models. Using a pedigree of 257 birds and 53, 111 single-nucleotide polymorphisms, we obtained high-density linkage and recombination maps for 25 autosomes and Z chromosome. The total sex-averaged linkage map was 1, 347 cM long, with the male map being 6.7% longer than the female map. Recombination maps revealed sexually dimorphic recombination rates (overall higher in males), with average recombination rate of 1.8 cM/Mb. Comparative analyses revealed high synteny of the helmeted honeyeater genome with that of 3 passerine species (e.g., 32 Hi-C scaffolds mapped to 30 zebra finch autosomes and Z chromosome). The genome assembly and linkage map suggest that the helmeted honeyeater exhibits a fission of chromosome 1A into 2 chromosomes relative to zebra finch. PSMC analysis showed a ∼15-fold decline in effective population size to ∼60, 000 from mid- to late Pleistocene. Conclusions: The annotated chromosome-length genome and high-density linkage map provide rich resources for evolutionary studies and will be fundamental in guiding conservation efforts for the helmeted honeyeater.